Efektifitas Program Pelayanan Identitas Kependudukan Digital di Kelurahan Simpang Tiga Pekan Kabupaten Serdang Bedagai - Gustiana, Zelfi Nanda; Pohan, Syafrudin (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
This research aims to examine the effectiveness of the Digital Population Identity service program in Serdang Bedagai Regency. One of the criteria for good public service is that the public service can be accepted by users of the service. This Digital Population Identity service program is a new innovation created by the Directorate General of Dukcapil, Ministry of Home Affairs, which aims to make it easier for people to use their identity. This research uses a qualitative approach with descriptive methods.